DEVELOPING STRATEGIC CSR AND NEGOTIATION ARCHITECTURE FOR THE ENX–FISHERMEN CONFLICT IN EAST KALIMANTAN - Movina Nasriati; Utomo Sarjono Putro (CV. Radja Publika, 2026)
There are still unresolved mediation issues between oil & gas operators in offshore areas where there are coastal communities depending on marine resources for their livelihood. The purpose of this research is to investigate mediation between the ENX oil and gas company and local fishermen who have been impacted negatively from the offshore operations of the ENX. This research will seek to determine both internal and external factors creating/ driving these negotiations and create strategies related to CSR and negotiating. Twelve semi-structured interviews were conducted with Company personnel, Government personnel, Fishermen and one independent informant. Thematic coding was used, however, the data analysis also utilized the frameworks of Stakeholder Theory, Legitimacy Theory, BATNA / ZOPA, PESTEL, SWOT, and TOWS. The results showed that compensation dominated the negotiations; whereas other integrative aspects including livelihood assurances, clarifying access to fishing areas and developing monitoring programs remained underdeveloped. Politics, society and economics were shown to be the major external factors contributing to the conflict. Based on the determination of the above factors, an Integrated CSR negotiation Model was proposed to include joint fact finding procedures, transparency within compensation arrangements, livelihood guarantees, formalized protocols for access to fishing areas and established monitoring mechanisms.